WEED INCIDENCE AND PROFITABILITY OF PEANUT (ARACHIS HYPOGAEA L.) AS AFFECTED BY PLANTING DENSITY AND INTEGRATED NUTRIENT APPLICATIONS - Santoral, Ina Michaela S; Cagasan, Ulysses A (Journal of Agriculture and Technology Management, 2023)
This study sought to evaluate the weed incidence and profitability of peanut production as affected by planting density and integrated nutrient applications. The experiment was laid out in a split-plot arranged in Randomized Complete Block Design (RCBD) with three replications. The different planting densities: D1 - 1 plant per hill and D2 – 2 plants per hill served as the main plot, and different fertilizer combination; N0 – Control (no fertilizer application), N1 – Inorganic fertilizer at 45-45-45 kgha-1 N, P2O5, K2O, N2– 5 tha-1 poultry litters + hyper plus foliar fertilizer, N3 –2.5 tha-1 poultry litters + 22.50-22.50-22.50 kgha-1 N, P2O5, K2O + hyfer plus foliar fertilizer, N4 – 5 tha-1 vermicomposts + hyper plus foliar fertilizer and N5 – 2.5 tha-1 vermicompost + 22.50-22.50-22.50 kgha-1 N, P2O5, K2O + hyfer plus foliar fertilizer as the sub plots. Results revealed that application of complete rate of inorganic fertilizer (45-45-45 kgha-1 N, P2O5, K2O) and 2.5 tha-1 poultry litters + 22.50 – 22.50 – 22.50 kgha-1 N, P2O5, K2O + 1 li foliar fertilizer ha-1) obtained the higher weed incidence and the heavier weeds` fresh weight than the other organically treated peanut plants. Likewise, the dominant weed species were the following for grasses: jungle rice ( Rottboellia cochinchinensis L.), barnyard grass ( Echinochloa crus-galli L.), Indian goosegrass ( Eleusine indica L.). while for sedges: flat sedge ( Cyperus compactus L.) and tall fringe rush ( Fimbristylis dichotoma L.) and for broadleaves: primrose willow ( Ludwigia octovalvis (Jacq.), garden spurge ( Euphorbia hirta L.) and spreading dayflower ( Commelina diffusa Burm.) On the other hand, different planting densities did not influence peanuts' yield characteristics. This means peanut production can be planted in single or double seeds per hill, but single seed per hill is more practical and advantageous. Likewise, different fertilizer combinations did not cause to vary in the yield parameters of peanut except for the non-marketable pod yield (tha-1). Moreover, an increase in the net return was noted in D2N0 with PHP 73,980.00 with 125% ROI, followed by D1N2 with PHP 56,082.40 and ROI of 94%.